"It's an emotional rollercoaster" the spatial and temporal structuring of affect in diagnosing childhood hearing loss. (November 2020) - Harris, Claire; Hemer, Susan R.; Chur-Hansen, Anna
Abstract: Despite well-established screening for hearing problems, and objective, diagnostic techniques aimed at dispelling uncertainty, some parents spend months waiting for clear diagnosis of their child's hearing loss. In the clinical setting, providers use international best-practice policies in diagnosing and managing childhood deafness, yet limited attention is given to the role of emotion in this context. Drawing on socio-spatial and temporal theories we conceptualise the clinical waiting room and soundproof booth of a paediatric hearing clinic as affective spacio-temporal places that both constrain and evoke emotion. Tensions between parents and professionals grew, and emotion and affect were problematised in the clinical setting where temporal notions held significance. We consider contentious or difficult areas in the management of childhood deafness through a number of cases of parents experiencing uncertainty as they grapple with decisions for their children. Alternative spaces and experiences in non-medical settings that hold value for parents are discussed in considering new approaches to managing childhood deafness. Highlights: Clinic waiting rooms & soundproof booths are affective temporal sites. The paediatric hearing clinic evokes and constrains emotions. Uncertainty and anxiety are managed as emotional labour in medical encounters. Uncertainty and anxiety in diagnostic medical spaces is experienced as sensory embodiment.